THE EFFECT OF FOREIGN DIRECT INVESTMENT ON TAX REVENUE IN DEVELOPING COUNTRIES - Arif Widya Pratomo (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2020)
The objective of this research paper is to study the effect of Foreign Direct Investment (FDI) on tax revenue in developing countries. FDI net inflow, greenfield, and brownfield FDI are selected as the independent variable, and tax revenue and its types are chosen as the dependent variable. Using panel data analysis, this research finds that FDI net inflow has a positive correlation on total tax revenue, corporate tax revenue, individual tax revenue, and VAT revenue. However, the effect of FDI net inflow on property tax revenue is not statistically significant. This research also finds that in the developing countries, the greenfield FDI has a beneficial effect on tax revenue while brownfield FDI tend to erode tax revenue. To deal with the possibility of endogeneity problems, this research uses “political stability and absence of violence” index as an instrumental variable and conducts a two-stage least square (2SLS) regression to estimate the parameter. The result shows that FDI has a positive correlation on total tax revenue, but not significant. However, the endogeneity test shows that the endogeneity problem is less likely to exist. To conclude, FDI and tax revenue tend to have only one direction effect from FDI to tax revenue.